The Harper–Hofstadter Hamiltonian and conical diffraction in photonic lattices with grating assisted tunneling - Tena Dubček; Karlo Lelas; Dario Jukić; Robert Pezer; Marin Soljačić; Hrvoje Buljan (New Journal of Physics, 2015)
We propose the realization of a grating assisted tunneling scheme for tunable synthetic magnetic fields in optically induced one- and two-dimensional dielectric photonic lattices. As a signature of the synthetic magnetic fields, we demonstrate conical diffraction patterns in particular realization of these lattices, which possess Dirac points in k -space. We compare the light propagation in these realistic (continuous) systems with the evolution in discrete models representing the Harper–Hofstadter Hamiltonian, and obtain excellent agreement.